FLORA DIVERSITY IN DEO CA SPECIAL USE FOREST PHU YEN PROVINCE - Van Phe, Phung (Journal of Forestry Science and Technology, 2023)
The Deo Ca Special Use Forest flora is quite diverse with 492 species belonging to 329 genera and 117 families of 4 vascular plant phyla. Of which, Magnoliophyta is the most dominant with 453 species (92.07%), 302 genera (91.79%), and 95 families (81.2%); the next Polypodiophyta with 32 species (6.5%), 21 genera (6.38%), 17 families (14.53%); the Lycopodiophyta has 4 species (0.81%) belonging to 3 genera (0.91%) of 2 families (1.71%); the last Pinophyta has 3 species (0.61%) belonging to 3 genera (0.91%) and 3 families (2.56%). In the Magnoliophyta, Magnoliopsida is more dominant than Liliopsida. The ratio of Magnoliopsida to Liliopsida in terms of the species, genus, and family are 8.44, 7.16, and 4.94, respectively. The ten most diverse plant families have 161 species, accounting for 32.72% and the ten most diverse genera have 56 species, representing 11.38% of the total species in the study site. The forest plant resources in the Deo Ca Special Use Forest area have a high diversity of use values and can be classified into 15 different groups of uses. There is a total of 28 threatened plant species in the study area, of which 17 are listed in the Vietnam Red Data Book and 18 are listed in Decree No. 84/2021/ND-CP, which need to be preserved.